Are your credits worthy?. Issue 1 (8th December 2012) - Lay, James R.; Long, Lisa A.; Marshall, Michael L.; Wanko, Jeffrey J.
<x xml:space="preserve">Abstract</x> Chemical and petrochemical manufacturing processes have potential for high consequence, low frequency events. Process safety management programs should identify and eliminate or control the conditions leading to the catastrophic hazards associated with these events. In recent years, industry has increasingly turned to quantitative or semiquantitative risk assessment tools to prioritize and manage the hazards they have identified. Risk assessment, whether qualitative, quantitative, or semiquantitative, is a powerful tool when used properly; however, companies must ensure that the safeguards for which they take credit are robust enough to truly manage hazards. This article discusses possible inconsistencies in process hazard analysis (PHA) claims. If a PHA claims credit for a good mechanical integrity (MI) program, what happens when that MI program has numerous deficiencies or violations? When a PHA bases a failure scenario frequency on industry historical experience, how does the site know that this experience is actually applicable to their processes? When a safeguard is challenged, is it available on‐demand? What are the consequences if a claimed safeguard does not perform as designed/credited? © 2012 American Institute of Chemical Engineers Process Saf Prog 32: 8–11, 2013